2015
DOI: 10.1080/10749357.2015.1110273
|View full text |Cite
|
Sign up to set email alerts
|

Post-stroke Fatigue is an Independent Predictor of Post-stroke Disability and Burden of Care: A Path analysis Study

Abstract: PSF, therefore, is an important determinant of post-stroke disability and should be evaluated for successful post-stroke rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Fatigue might be assessed as a mediator of this longitudinally. Post-stroke fatigue and depression had overlapping yet distinct effects on functional outcome measures; these findings add to a path analysis study on disability among stroke survivors (Mandliya et al, 2016 ). The current results underscore the importance of recognizing fatigue clinically, and the need to understand the underlying pathophysiology.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Fatigue might be assessed as a mediator of this longitudinally. Post-stroke fatigue and depression had overlapping yet distinct effects on functional outcome measures; these findings add to a path analysis study on disability among stroke survivors (Mandliya et al, 2016 ). The current results underscore the importance of recognizing fatigue clinically, and the need to understand the underlying pathophysiology.…”
Section: Discussionsupporting
confidence: 52%
“…Fatigue influences mobility (Ponchel et al, 2015 ), as measured using the Berg Balance Scale (BBS) or mobility tests (Michael et al, 2006 ; Duncan et al, 2015 ). There remains a need to dissect the complex inter-relationships between these prevalent sequelae and cognitive and mobility outcomes (Mandliya et al, 2016 ). There is little evidence that post-stroke fatigue is directly associated with cognition; however, a recent synthesis of evidence suggested that fatigue may heighten the influence of depressive symptoms (Ponchel et al, 2015 ), and therefore, there may be an indirect relationship between fatigue and cognition that is mediated by depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Of the patients with a first stroke, up to 75% will suffer PSF in the first year following stroke [1]. PSF has a detrimental impact on the recovery of neurological function, quality of life and rehabilitation of stroke survivors [2][3][4][5]. However, the pathogenesis of PSF remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Stroke was known as the leading cause of adult disability and resulted in great social burden [1,2]. Approximately a third of stroke patients suffered from the recurrence of stroke, and 75 % of them had cardiac disease [3,4].…”
Section: Introductionmentioning
confidence: 99%